Twinning the legitimacy of governments with the principles of good governance in the Kurdistan Region: An analytical study - Esmael Najmadin Zangana; Sirwan Hamd Ahmed; Aso Hamashin Abdulkareem (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
The principles of good government inside a country, is one of the most important governing criteria of each country on the international level, Thus, giving the feature of governing to each government depends on the commitment of that government to the specific principles of good governing in order to let the government reach the authority and its application. So, this study attempts to investigate the tight relationship between good government and legitimacy which are two important concepts of statehood. Each one of them can impact on another one directly. i.e., if the government commits to a free election as a good governing principle leads to giving legitimacy to that government to reach the authority and become a state. On the other hand, committing the government to respect the authoritative law and applying the law on every one equally and working within the constitution to lead the conspiracy of decision making and income and expenses and respecting the principles of human rights which are principles of good government which gives the legitimacy feature to governments and applying their authorities.